2014
DOI: 10.1136/bjsports-2014-5555rep
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for lower limb osteoarthritis: systematic review incorporating trial sequential analysis and network meta-analysis

Abstract: Objective To determine whether there is sufficient evidence to conclude that exercise interventions are more effective than no exercise control and to compare the effectiveness of different exercise interventions in relieving pain and improving function in patients with lower limb osteoarthritis. Data sources Nine electronic databases searched from inception to March 2012.Study selection Randomised controlled trials comparing exercise interventions with each other or with no exercise control for adults with kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 15 publications
4
125
1
4
Order By: Relevance
“…Related to the inflammatory hypothesis, sedentary behaviour is also associated with inflammation (Hamer et al, 2012a, Hamer et al, 2012b and both pain (Stubbs et al, 2014) and depression are associated with sedentary behaviour . Given that physical activity can improve inflammatory markers (Hamer et al, 2014), interventions increasing activity levels may improve pain symptoms (Uthman et al, 2013) and depression (Schuch et al, 2016a, Schuch et al, 2016b and at a population level may be a particularly viable option in LMICs. Another potential option is that areas of the brain linked to mood dysregulation (e.g.…”
Section: General Findingsmentioning
confidence: 99%
“…Related to the inflammatory hypothesis, sedentary behaviour is also associated with inflammation (Hamer et al, 2012a, Hamer et al, 2012b and both pain (Stubbs et al, 2014) and depression are associated with sedentary behaviour . Given that physical activity can improve inflammatory markers (Hamer et al, 2014), interventions increasing activity levels may improve pain symptoms (Uthman et al, 2013) and depression (Schuch et al, 2016a, Schuch et al, 2016b and at a population level may be a particularly viable option in LMICs. Another potential option is that areas of the brain linked to mood dysregulation (e.g.…”
Section: General Findingsmentioning
confidence: 99%
“…Muscular endurance training has been explored as an intervention to prevent or delay OA onset (10,16). Considering the lower limb as an integrated unit, the use of exercises for developing strength of the quadriceps, hamstrings, abdominals, and gluteus medius and maximus can lead to normal biomechanical restoration of the lower limb and promote OA symptom control.…”
Section: Introductionmentioning
confidence: 99%
“…While certain authors suggest that a simple flexion-extension exercise program is sufficient to achieve positive results in treatment, 16 there is stronger evidence to suggest that a combination of various forms of exercises is most beneficial, although it is still unclear which exercise combinations work best. 13,31 Furthermore, most functional outcome parameters are seen to improve with these interventions except pain and knee adduction moment, that show little improvement at long-term follow-up. More high quality systemic reviews addressing exercise therapy interventions are needed for narrowing down optimum interventions, and would make it easier for healthcare professionals to design the most effective intervention programs.…”
Section: Resultsmentioning
confidence: 99%
“…Ni et al 30 demonstrated similar results in a study demonstrating the efficacy of Tai Chi on improving function in cases of Knee OA. However in both these studies the control groups did not undergo any form of physical exercises, and since studies have shown benefits of physical exercises in OA 13,31 it is difficult to say whether Tai Chi is more effective than standard exercises. Nonetheless it is a safe and controlled form of training and can be incorporated in a rehabilitation program, as it has not shown any adverse effects.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation